Inside the tape recorder factory. (22nd June 2022) - Burkhart, Benjamin
Abstract : Technical media such as playback devices play a key role in popular music culture. Hence, it is hardly surprising that extensive cultural-historical research with a focus on such devices has already been conducted. But almost all researchers working on the cultural history of playback devices in Germany concentrate on West Germany, while the media history of the GDR is treated marginally. In this article, I aim to contribute to the historiography of the GDR's popular music with a focus on material culture. In doing so, I analyse archival material of the state-owned company VEB Messgerätewerk Zwönitz, which manufactured tape recorders in the 1950s and 1960s. The focus is on documents regarding the tape recorder BG 20. The sources, for example technical reports, advertisements, and letters from the government, demonstrate that the manufacturing of music devices in the GDR was highly influenced by the political conditions.